The Unclear Employment Status of Digital Platform Workers in the Indonesian Labor Law System - Riko Adamulloh, Muhammad; Adam, Mustopa; Suandi, Suandi; Rizki Aji Putra, Gilang (BULETIN ADALAH, 2025)
The development of the digital economy has given rise to a platform-based employment relationship model (gig economy), which places workers in an ambiguous position within the Indonesian labor law system. This article aims to analyze the unclear employment status of digital platform workers from the perspective of Indonesian labor law and formulate ideas for a more adaptive and equitable regulatory reconstruction. This research employs normative legal research methods, utilizing a statutory and conceptual approach. The results indicate that the provisions in Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning Job Creation, do not explicitly accommodate platform-based employment models. This unclear status results in the non-fulfillment of workers' normative rights, such as minimum wages, social security, and protection against termination of employment. Regulatory reconstruction is needed to clarify the category of digital employment relationships, ensuring legal certainty and protecting workers' rights. Keywords: Digital Platform Workers, Employment Relations, Gig Economy, Legal Protection, Regulatory Reform